Genetic variation of three wild zebrafish population (Danio rerio) in Bangladesh - Islam, Md Khademul; Badruddoza, Md; Salam, Sumaiya Binte; Alam, Mohammad Shamimul; Kabir, Md Alamgir; Rabbane, Md Golam (Frontiers in Ecology and Evolution, 2025)
Morphological and genetic diversity of three wild zebrafish populations in Bangladesh (Rangpur, Netrokona, and Cumilla) were elucidated using DNA barcoding and Random Amplified Polymorphic DNA (RAPD). Morphometric variation was minimal therefore, RAPD profiling and DNA barcoding were also used. Total 236 bands, including 29 polymorphic bands and 2 unique bands in RAPD showed 14.09% polymorphism indicating a low genetic diversity among them. Genetic distances were ranged from 0.0048 to 0.1031, with the highest genetic distance between Rangpur and Netrokona populations. DNA barcoding showed 99% similarity to Danio rerio from the GenBank, and multiple sequence alignment confirmed high genetic similarity (99.41) among these populations. Phylogenetic analysis showed these three zebrafish populations were grouped into distinct clusters, supporting the presence of genetic structure across populations. These information provides an essential reference data for the conservation, management, and potential selective breeding of zebrafish. The findings of this research also emphasize the efficacy of DNA barcoding and RAPD as complementary methods in the study of population genetics.